Pythagoras and the National Hockey League - Cochran, J. J.; Blackstock, R. (Journal of Quantitative Analysis in Sports, 2009)
The nature of the relationship Bill James found between the win/loss percentage of a Major League Baseball team and the number of runs the team scores and allows over the course of a season is investigated for the National Hockey League (NHL). We find the optimal form of James' model for the NHL using the absolute error criterion and demonstrate that far more complex forms of James' model yield little in additional predictive power. We also provide empirical evidence that the relationship between win/loss percentage and goals scored and allowed varies relatively little across recent seasons.